Coordination dynamics in a socially situated nervous system - Coey, Charles A.; Varlet, Manuel; Richardson, Michael J. (Frontiers in Human Neuroscience, 2012)
Traditional theories of cognitive science have typically accounted for the organization of human behavior by detailing the requisite computational or representational functions and identifying neurological mechanisms that might perform these functions. Put simply, such approaches hold that neural activity causes behavior. This same general framework has been extended to accounts of human social behavior via explanatory concepts such as “common-coding” and “co-representation”, and much recent neurological research has been devoted to brain structures that might execute these social-cognitive functions. Although these neural processes are unquestionably involved in the organization of human social interactions, there is good reason to question whether they should be accorded causal primacy. Specifically, research on interpersonal rhythmic motor coordination suggests that the organization of human behavior, including social behavior, can result from self-organizing processes and the lawful dynamics of animal-environment systems. Here we review this research, and in doing so propose that the role of the nervous system in joint action and interpersonal coordination be recast from the sole cause of behavior to one of many interdependent processes.